Towards a secure and available smart grid using intrusion tolerance. - Tanha, Maryam; Hashim, Fazirulhisyam (Springer Berlin, 2012)
An intrusion tolerant architecture to enhance the security of smart grid control centers. The proposed architecture is mainly composed of several modules, including replication and diversity, auditing, compromised/faulty replica detector, reconfiguration and proxy. These modules attempt to enhance the service continuity and availability of critical components in smart grid control centers due to far-reaching, economic and destructive effects of failure, malfunction, power brownout or outage on the normal operation of societies. By adopting a combination of proactive and reactive security measures to tolerate and mitigate the impacts of intrusions, the presented intrusion tolerant system shows improved availability in case of DoS attacks when analytically evaluated and compared with two well-known intrusion tolerant architectures.